2014
DOI: 10.1093/infdis/jiu040
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes Among Persons With Pulmonary Tuberculosis Caused by Mycobacterium tuberculosis Isolates With Phenotypic Heterogeneity in Results of Drug-Susceptibility Tests

Abstract: Phenotypic DST heterogeneity among persons with HIV infection who are being treated for MDR tuberculosis is associated with poor outcomes and longer times to culture conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…Our results are in agreement with a previous study which have demonstrated that infections with heteroresistance can compromise treatment outcomes14. In contrast, Cohen et al .…”
Section: Discussionsupporting
confidence: 94%
“…Our results are in agreement with a previous study which have demonstrated that infections with heteroresistance can compromise treatment outcomes14. In contrast, Cohen et al .…”
Section: Discussionsupporting
confidence: 94%
“…These scenarios lead to so-called heteroresistance, which is encountered in 7-25% of patients with MDR tuberculosis, patients previously treated for tuberculosis, and those in whom first-line therapy failed. 70,205,206 Treatment with standard regimens or MDR tuberculosis regimens would lead to rapid selection of the drugresistant subpopulations, either on the basis of classic Luria-Delbrück considerations, or the antibiotic resistance process shown in figure 5. 207 Redefining drug resistance, MDR tuberculosis, and XDR tuberculosis by changing susceptibility breakpoints M tuberculosis is considered drug resistant when >1% of M tuberculosis cultures grow in the presence of critical drug concentrations.…”
Section: The Role Of Efflux Pumps In Antibiotic Resistancementioning
confidence: 99%
“…While M. tuberculosis primarily causes lung infections, it can disseminate to extrapulmonary organs, particularly in subjects co-infected with HIV. Understanding how M. tuberculosis diversifies and spreads within individuals is crucial to outbreak tracing 11 , clinical diagnosis of resistance 1214 , and designing strategies to minimize de novo emergence of antibiotic resistance 1517 .…”
mentioning
confidence: 99%